Bioinformatic Analyses of Canonical Pathways of TSPOAP1 and its Roles in Human Diseases - Suthar, Sharad Kumar; Alam, Mohammad Maqusood; Lee, Jihye; Monga, Jitender; Joseph, Alex; Lee, Sang-Yoon (Frontiers in Molecular Biosciences, 2021)
TSPO-associated protein 1 (TSPOAP1) is a cytoplasmic protein and is closely associated with its mitochondrial transmembrane protein partner translocator protein (TSPO). To decipher the canonical signalling pathways of TSPOAP1, its role in human diseases and disorders, and relationship with TSPO; expression analyses of TSPOAP1- and TSPO-associated human genes were performed by a Qiagen Ingenuity Pathway Analysis (IPA). In the expression analysis, necroptosis and sirtuin signalling pathways, mitochondrial dysfunction, and inflammasome were the top canonical pathways for both TSPOAP1 and TSPO, confirming the close relationship between these two proteins. A distribution analysis of common proteins in all the canonical pathways predicted for TSPOAP1 revealed that tumor necrosis factor receptor 1 (TNFR1), vascular cell adhesion molecule 1 (VCAM1), cyclic AMP response element-binding protein 1 (CREB1), T-cell receptor (TCR), nucleotide-binding oligomerization domain, leucine-rich repeat and pyrin domain containing 3 (NLRP3), DNA-dependent protein kinase (DNA-PK or PRKDC), and mitochondrial permeability transition pore (mPTP) were the major interaction partners of TSPOAP1, highlighting the role of TSPOSAP1 in inflammation, particularly neuroinflammation. An analysis of the overlap between TSPO and TSPOAP1 Homo sapiens genes and top-ranked canonical pathways indicated that TSPO and TSPOAP1 interact via voltage-dependent anion-selective channels (VDAC1/2/3). A heat map analysis indicated that TSPOAP1 has critical roles in inflammatory, neuroinflammatory, psychiatric, and metabolic diseases and disorders, and cancer. Taken together, this information improves our understanding of the mechanism of action and biological functions of TSPOAP1 as well as its relationship with TSPO; furthermore, these results could provide new directions for in-depth functional studies of TSPOAP1 aimed at unmasking its detailed functions.